First Precambrian palaeomagnetic data from the Mawson Craton (East Antarctica) and tectonic implications. Issue 1 (December 2018) - Liu, Yebo; Li, Zheng-Xiang; Pisarevsky, Sergei; Kirscher, Uwe; Mitchell, Ross; Stark, J.; Clark, Chris; Hand, Martin
Abstract A pilot palaeomagnetic study was conducted on the recently dated within situ SHRIMP U-Pb method at 1134 ± 9 Ma (U-Pb, zircon and baddeleyite) Bunger Hills dykes of the Mawson Craton (East Antarctica). Of the six dykes sampled, three revealed meaningful results providing the first well-dated Mesoproterozoic palaeopole at 40.5°S, 150.1°E (A95  = 20°) for the Mawson Craton. Discordance between this new pole and two roughly coeval poles from Dronning Maud Land and Coats Land (East Antarctica) demonstrates that these two terranes were not rigidly connected to the Mawson Craton ca. 1134 Ma. Comparison between the new pole and that of the broadly coeval Lakeview dolerite from the North Australian Craton supports the putative ~40° late Neoproterozoic relative rotation between the North Australian Craton and the combined South and West Australian cratons. A mean ca. 1134 Ma pole for the Proto-Australia Craton is calculated by combining our new pole and that of the Lakeview dolerite after restoring the 40° intracontinental rotation. A comparison of this mean pole with the roughly coeval Abitibi dykes pole from Laurentia confirms that the SWEAT reconstruction of Australia and Laurentia was not viable for ca. 1134 Ma.